2008
DOI: 10.1007/s00259-008-0739-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPT-induced monoamine depletion in humans: evaluation of two alternative [123I]IBZM SPECT procedures

Abstract: Purpose Acute monoamine depletion paradigms using alpha-methyl-para-tyrosine (AMPT) combined with single photon emission computed tomography (SPECT) have been used successfully to evaluate disturbances in central dopaminergic neurotransmission. However, severe side effects due to relatively high doses (4,500 to 8,000 mg) of AMPT have been reasons for study withdrawal. Thus, we assessed the effectiveness and tolerability of two alternative procedures, using lower doses of AMPT. Methods Six healthy subjects unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…DAT binding in PD is commonly asymmetric, and the loss of binding is generally more profound in the putamen than in the caudate nucleus, which is also the case in this study, thus confirming the findings of earlier DAT SPECT studies in PD [20,23]. We hypothesized that if dopamine would be taken up predominantly by serotonergic neurons, then this phenomenon would first occur in the most affected striatal area.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…DAT binding in PD is commonly asymmetric, and the loss of binding is generally more profound in the putamen than in the caudate nucleus, which is also the case in this study, thus confirming the findings of earlier DAT SPECT studies in PD [20,23]. We hypothesized that if dopamine would be taken up predominantly by serotonergic neurons, then this phenomenon would first occur in the most affected striatal area.…”
Section: Discussionsupporting
confidence: 90%
“…Image acquisition was performed 24 h after injection. Images were corrected for attenuation and reconstructed in 3D [22,23]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it is important to note that AMPT can produce serious dose-related side effects, including crystalluria and acute dystonia (Abi-Dargham et al, 2000; Voruganti et al, 2001). Future studies should therefore also investigate low-dosage regimens, which have been demonstrated to be a suitable alternative that is free from severe side effects (Boot et al, 2008). Thus, it is possible to conduct cross-species relevant studies in animals and humans with previous studies supporting our findings that AMPT can reduce mania-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nondisplaceable binding potential (BP ND ) was calculated as follows: (mean striatal binding-mean binding occipital cortex)/mean binding occipital cortex. Standard templates with fixed ROIs were positioned on the striatum and occipital cortex (reflecting non-specific binding), as earlier described (Booij et al, 1997;Boot et al, 2008). dAMPHinduced decrease in […”
Section: Spect Acquisition and Processingmentioning
confidence: 99%
“…SPECT images were corrected for attenuation and reconstructed using iterative algorithms, as earlier described (Booij et al, 1997;Boot et al, 2008). Nondisplaceable binding potential (BP ND ) was calculated as follows: (mean striatal binding-mean binding occipital cortex)/mean binding occipital cortex.…”
Section: Spect Acquisition and Processingmentioning
confidence: 99%